MODEL MEMBANGUN DESA MANDIRI - Harjo, Budi (JURNAL SOSIAL DAN HUMANIS SAINS, 2017)
The village as an entity that until now still lagging behind in development has received great attention from various circles, both the government itself and the Non-Governmental Organization and Higher Education. But building up the village that has been done with the assumption that "money" is the main factor of development, proved unsuccessful to raise the village to be more prosperous, and independent, so it is necessary joint efforts, simultaneously, from various circles to share roles in building the village, the other paradigm, the village build, so the village asset becomes the main factor in building the village.